Pathways towards break even for low convergence ratio direct-drive inertial confinement fusion. (21st June 2022) - Paddock, R.W.; Martin, H.; Ruskov, R.T.; Scott, R.H.H.; Garbett, W.; Haines, B.M.; Zylstra, A.B.; Campbell, E.M.; Collins, T.J.B.; Craxton, R.S.; Thomas, C.A.; Goncharov, V.N.; et al.
Abstract : Following indirect-drive experiments which demonstrated promising performance for low convergence ratios (below 17), previous direct-drive simulations identified a fusion-relevant regime which is expected to be robust to hydrodynamic instability growth. This paper expands these results with simulated implosions at lower energies of 100 and 270 kJ, and 'hydrodynamic equivalent' capsules which demonstrate comparable convergence ratio, implosion velocity and in-flight aspect ratio without the need for cryogenic cooling, which would allow the assumptions of one-dimensional-like performance to be tested on current facilities. A range of techniques to improve performance within this regime are then investigated, including the use of two-colour and deep ultraviolet laser pulses. Finally, further simulations demonstrate that the deposition of electron energy into the hotspot of a low convergence ratio implosion through auxiliary heating also leads to significant increases in yield. Results include break even for 1.1 MJ of total energy input (including an estimated 370 kJ of short-pulse laser energy to produce electron beams for the auxiliary heating), but are found to be highly dependent upon the efficiency with which electron beams can be created and transported to the hotspot to drive the heating mechanism.